Who is thinking of leaving Germany? The role of postmaterialism, risk attitudes, and life-satisfaction on emigration intentions of German nationals - Elena Samarsky (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
The subject of emigration from affluent countries, such as Germany, raises the question of who are more likely to leave their highly-industrialized countries known for high living standards, stable political scene and prosperous economy. Using the theory of postmaterialism (Inglehart, 1997) this paper explores emigration intentions of German nationals taking into account country's specific socio-economic context through the value sets of its nationals. By analyzing emigration intentions of German nationals recorded by the German SocioEconomic Panel (SOEP) the findings link postmaterialism theory to emigration intentions, and show that those who express emigration intentions are more likely to have postmaterialistic values than materialistic or mixed values. Furthermore, when controlling for life-satisfaction and risk attitudes, the effect of postmaterialistic and materialistic values on intentions to emigrate remain significant. Lastly, the analysis corroborates other studies by showing that those who display emigration intentions also more likely to have higher risk tolerance and lower life-satisfaction.
Keywords: 330; migration intentions; value set; risk attitudes; life-satisfaction; Germany